Hot isostatic pressing of MgAlON transparent ceramic from carbothermal powder. Issue 4 (March 2018) - Ma, Benyuan; Zhang, Wei; Wang, Yuezhong; Xie, Xiumin; Song, Haizhi; Yao, Chao; Zhang, Zhibin; Xu, Qiang
Abstract: Highly transparent MgAlON ceramic was prepared by hot isostatic pressing (HIP) of the presintered compact using the MgAlON powder synthesized by carbothermal reduction and nitridation (CRN) method. Fine and low agglomerated MgAlON powder was synthesized at a relatively low temperature (1600 °C) for 2 h under N2 atmosphere. The MgAlON powder showed high sinterability with a bimodal particle size distribution at 0.3 µm and 0.7 µm. MgAlON ceramics were fabricated by pressureless presintering at 1840 °C for 10 h in N2 atmosphere and HIP at 1880 °C for 2 h in 190 MPa Ar gas. The HIPed ceramic was fully dense with average grain sizes 50 µm. The in-line transmittance of the HIPed sample reached 81.2% at 400 nm and 84.1% at 2500 nm, respectively. The Vickers hardness and flexural strength of highly transparent MgAlON ceramic were 13.74 ± 0.15 GPa and 268 ± 7 MPa, respectively. The results demonstrate that our method has a promising future in transparent MgAlON ceramic production.